Glass Imprint Templates by Spark Assisted Chemical Engraving for Microfabrication by Hot Embossing - Lucas Abia Hof; Xin Guo; Minseok Seo; Rolf Wüthrich; Jesse Greener (Micromachines, 2017)
As the field of microelectromechanical systems (MEMS) matures, new demands are being placed on the microfabrication of complex architectures in robust materials, such as hard plastics. Iterative design optimization in a timely manner—rapid prototyping—places challenges on template fabrication, for methods such as injection moulding and hot embossing. In this paper, we demonstrate the possibility of using spark assisted chemical engraving (SACE) to produce micro patterned glass templates. The direct, write-based approach enabled the facile fabrication of smooth microfeatures with variations in all three-dimensions, which could be replicated by hot embossing different thermoplastics. As a proof of principle, we demonstrated the technique for a high glass transition temperature polycarbonate. Good fidelity over more than 10 cycles provides evidence that the approach is viable for rapid prototyping and has the potential to satisfy commercial-grade production at medium-level output volumes. Glass imprint templates showed no degradation after use, but care must be taken due to brittleness. The technique has the potential to advance microfabrication needs in academia and could be used by MEMS product developers.